Nonhuman Witnessing: War, Data, and Ecology after the End of the World - Richardson, Michael (Thought in the Act : 18, 2024)
In Nonhuman Witnessing Michael Richardson argues that a radical rethinking of what counts as witnessing is central to building frameworks for justice in an era of endless war, ecological catastrophe, and technological capture. Dismantling the primacy and notion of traditional human-based forms of witnessing, Richardson shows how ecological, machinic, and algorithmic forms of witnessing can help us better understand contemporary crises. He examines the media-specificity of nonhuman witnessing across an array of sites, from nuclear testing on First Nations land and autonomous drone warfare to deepfakes, artificial intelligence, and algorithmic investigative tools. Throughout, he illuminates the ethical and political implications of witnessing in an age of profound instability. By challenging readers to rethink their understanding of witnessing, testimony, and trauma in the context of interconnected crises, Richardson reveals the complex entanglements between witnessing and violence and the human and the nonhuman.